A hybrid type I randomized effectiveness-implementation trial of a Naturalistic Developmental Behavioral Intervention in the Part C early intervention system: study protocol - Allison L. Wainer; Sarah R. Edmunds; Alice S. Carter; Wendy L. Stone; R. Christopher Sheldrick; Sarabeth Broder-Fingert; Yael S. Stern; Ellie Harrington; Lisa V. Ibanez; Brooke Ingersoll (BMC Pediatrics)
Abstract Background Participation in Naturalistic Developmental Behavioral Interventions (NDBI) is associated with significant improvements in functioning for toddlers with, and showing early signs of, autism spectrum disorder. The Part C Early Intervention (EI) system, which is publicly funded and available in all U.S. states, offers an optimal infrastructure through which toddlers can receive NDBIs. This study seeks to assess the effectiveness and fit of one NDBI, Caregiver Implemented Reciprocal Imitation Teaching (CI-RIT), within the Part C EI system. Methods This hybrid type 1 effectiveness/implementation trial uses a multi-site randomized control design to simultaneously test effectiveness and collect implementation data on CI-RIT in the Part C EI system across four states: Illinois, Massachusetts, Michigan and Washington. Participants include EI providers (target n = 160) who are randomized to either CI-RIT or treatment as usual (TAU), and child/caregiver dyads on their caseloads (target n = 440). Primary effectiveness outcomes focus on (1) child social communication, joint attention, motor imitation; and (2) caregiver responsivity, implementation fidelity of RIT, and self-efficacy, which are all measured at baseline and then 4-months and 9-months after baseline. Implementation outcomes include CI-RIT modifications, treatment acceptability, fidelity of CI-RIT coaching, and RIT session completion. Discussion This study represents a critical effort to transport an evidence-based NDBI, CI-RIT, into a national service delivery setting, the Part C EI system. The large, multi-site nature of the trial provides the opportunity to address critical questions about training and intervention effectiveness, which will, in turn, optimize and support CI-RIT implementation at scale. Trial registration The trial protocol is registered at ClinicalTrials.gov (NCT05114538; Registration date: 10/28/2021).